METHODS OF PHYSICAL CULTURE AND HEALTH-IMPROVING CLASSES WITH ELEMENTS OF MARTIAL ARTS FOR MEN WHO LEAD A SEDENTARY LIFESTYLE - Cherkashin I.A.; Peijun Huang; Platonov D.N.; Platonova L.L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was the theoretical and experimental substantiation of the methodology of physical culture and health-improving classes with elements of martial arts for men aged 40-60 years who lead a sedentary lifestyle. Methods and structure of the study. The experiment involved 60 men aged 40-60 years (48.07±6.22), who were divided into experimental (EG) and control (CG) groups of 30 people. The men of the experimental group attended classes conducted in accordance with the developed methodology of physical culture and health improvement with elements of martial arts. Representatives of the control group were engaged in a different program, the basis of which was running in an aerobic mode. The method of cardiointervalometry was used to monitor the functional state and the risk of sudden cardiac death, the method of bioimpedancemetry was used to assess the component composition of the body. Results and conclusions. At the end of the one-year experiment in the EG, the percentage of men with an above average and high level of functional state increased from 20.0 to 50.0% and from 6.7 to 16.6%, respectively, and in this group, 27 people showed a decrease in risk sudden cardiac death. An analysis of intergroup differences in indicators of body composition showed that the body fat content significantly decreased in the experimental group compared to the CG, the change was 12.4% (p<0.05), a decrease in fat content in the arms, legs and torso was noted, changes in which varied in the range from 7.2 to 12.4% (p<0.05). Consequently, the application of the developed methodology of physical culture and health-improving classes with elements of martial arts for men aged 40-60, leading a sedentary lifestyle, made it possible to increase the level of functional state, reduce the risk of sudden cardiac death, adjust the body weight and component composition of the body involved.